How does playing position affect fatigue-induced changes in high-intensity locomotor and micro-movements patterns during professional rugby union games? - Fornasier-Santos, C.; Millet, G. P.; Stridgeon, P.; Brocherie, F.; Girard, O.; Nottin, S. (European Journal of Sport Science, 2021)
We questioned whether changes in high-intensity locomotor and micro-movements patterns between the first and second part of each half depend on playing position in the 2014-2015 European rugby union championship winning team. Thirty-three rugby players were grouped according to five playing positions. Players were equipped with micro-electromechanical system including a GPS sampling at 10 Hz and high temporal resolution micro-sensors during 17 Top14 and 7 European games. High-speed movements (HSM), high-intensity accelerations (HIA), repeated high-intensity efforts (RHIE), and high-intensity micro-movements (HIMM) were subsequently compared between four 20-min game periods. No significant group × time interactions were observed for any locomotor variables (p > 0.283). Irrespectively of playing position, the number of HSM (p = 0.019), decreased from 0-20 min to 60-80 min as well as from 40-60 to 60-80 min (p < 0.001) with HIA (p = 0.020) and RHIE (p < 0.001). Significant group × time interaction was found for HIMM (p = 0.03) with a significant decrease observed in back row forwards from 0-20 to 60-80 min periods (-17.5%; ES = 0.6; p = 0.031). In elite rugby union, fatigue-induced changes during the last 20 min are independent from playing positions in high-intensity locomotor patterns in contrary to HIMM. Training drills that include specific RHIE (high-speed and HIA efforts) may be useful to postpone match-related fatigue.